Intrawound Vancomycin Powder in Primary Total Hip Arthroplasty Increases Rate of Sterile Wound Complications - Dial, Brian L. (Hip Pelvis, 2018)
PURPOSE: Total hip arthroplasty (THA) is a successful surgery for the treatment of hip osteoarthritis; however, the risk of a post-operative prosthetic joint infection (PJI) remains at 1% to 2%. The purpose of this study was to investigate the safety profile of using vancomycin powder (VP) to reduce infection rates by reviewing acute postoperative complications. MATERIALS AND METHODS: A retrospective review of 265 consecutive patients undergoing THA was performed. The first 128 patients, the control group, did not receive VP, and the subsequent 137 patients, the VP group, received VP at the time of wound closure. Patient demographic data, medical comorbidities, and perioperative information were compared. RESULTS: The primary outcome was a post-operative surgical complication within 90 days from surgery. The control and VP group's demographic, medical comorbidities and perioperative information data were statistically similar. Deep infection rate in the control group was 5.5%, whereas the deep infection rate in the VP group was 0.7% (P=0.031). Sterile wound complication rate was 4.4% in the VP group, and 0% in the control group (P=0.030). Remaining complications were not statistically different between the groups. CONCLUSION: VP was associated with an increase rate of sterile wound complications compared to the control group. The rate of PJI was decreased with the use of VP. We do not recommend for or against the use of VP at time of wound closure to prevent PJI, and higher powered studies will need to be performed to demonstrate the efficacy of VP.